A basic guide to eschatology : making sense of the millennium - Erickson, Millard J. (Grand Rapids, MI Baker Books, 1998)
At the turn of the millennium, when increasing attention is being given to eschatological subjects, there is a need for an objective, comprehensive overview of the various end-times perspectives. A Basic Guide to Eschatology is such a resource. In this accessible study, leading evangelical theologian Millard Erickson provides a balanced examination of various eschatological viewpoints. - Back cover.
Introduction -- Part one : Background views. Schweitzer and Dodd -- Bultmann and Moltmann -- Part two : Millennial views. Postmillennialism -- Amillennialism -- Premillennialism -- Part three : Tribulational views. Dispensationalism -- Pretribulationism -- Posttribulationism -- Mediating positions -- Conclusion.
Revised edition of: Contemporary options in eschatology, 1977.
Includes bibliographical references (pages 185-189) and indexes.
Keywords: Millennium (Eschatology); Eschatology -- History of doctrines